Endovascular Treatment of Posttraumatic Pseudoaneurysm of the Common Carotid Artery - Diego Rojas; Stefan Stefanov; Luis Riera del Moral; Jesús Álvarez; Luis Riera de Cubas (Case Reports in Vascular Medicine)
Carotid artery injuries with pseudoaneurysm are uncommon but associated with central neurologic dysfunction. We present a case of posttraumatic pseudoaneurysm of the right common carotid artery treated by implantation of a covered stent. A 44-year-old woman with multiple injuries after fall from height presents a small dissection flap of the right common carotid artery (RCCA) on the initial computed tomography angiography (CTA). Fifteen days later a 10 mm pseudoaneurysm is observed on control CTA. We decided endovascular treatment. Through right femoral access with a long introducer sheath placed in the innominate artery, we implanted a covered stent Advanta V12 9×38 mm in the RCCA. The patient was discharged from the hospital with antiplatelet therapy without any neurological dysfunction and complete exclusion of the pseudoaneurysm. Use of covered stents has emerged as a safe and effective alternative to surgical repair of carotid injuries.